Hubungan stres dengan Kualitas Hidup pada Penderita DM Tipe 2 di Kabupaten Poso - Tampai, Dwi Debi; Lainsamputty, Ferdy; Katiandagho, Yunike (Journal of Islamic Medicine, 2021)
Background: DM and stress are closely related especially to events in urban areas. Life pressures and unhealthy lifestyles are very influential, coupled with increasingly rapid technological advances and various diseases that are being suffered causing a decrease in a person's condition so that it triggers stress. Psychological disorders such as depression and stress that are common in the DM population, require proper treatment because they cause a drastic reduction in quality of life. Objective: This research was conducted to determine the relationship between stress and quality of life in patients with type 2 diabetes. Method: This research is a correlation analytic type with a cross sectional approach. The population in this study were all patients with type 2 DM in outpatients in Poso Regional Hospital as many as 2023 people, with a total sample of 137 people. The sampling technique used was purposive sampling. Data were collected using a Depression Anxiety Stress Scale 42 (DASS 42) and WHOQOL-BREF questionnaire. Descriptive statistics and bivariate analysis (mann whitney, kruskalwallis and Spearman Rank) are used to look for relationships between variables. Results: Age related to quality of life in the physical domain (p0.05), duration (long suffering from type-2 diabetes mellitus) was associated with quality of life in the physical domain (p0.01), stress had no relationship when associated with all quality-of-life domains. (p0.05). Conclusion: There is no relationship between stress and quality of life in type 2 DM patientsKeyword :Quality of Life DM type 2, Stress